A sensitive colorimetric biosensor based on intermolecular split G-quadruplex DNAzymes and magnetic nanoparticles for the detection of Hg2+. Issue 6 (October 2016) - Zhang, Wei; Tang, Yujiao; Shao, Shuang; Dai, Shiyan; Cheng*, Guifang; He, Pingang; ,; Fang, Yuzhi
No abstract available